Artificial intelligence in information management: transforming information retrieval, classification, and management systems - Ismail, Azratul Ain Nadiah; Mat Yatin, Saiful Farik; Mustakin, Nur Imana; Mustafa Kamal, Aina Musfirah; Daud, Roslaizam (Faculty of Information Management, 2025)
The integration of Artificial Intelligence (AI) into information management improves efficiency, system reliability, and decision-making. This article examines how AI enhances information retrieval accuracy, classification precision, and impacts knowledge accessibility and data management. Using a literature review, the study highlights AI techniques like machine learning and natural language processing, which improve indexing, categorization, and retrieval, boosting performance. Ethical challenges, such as data privacy and algorithmic bias, require attention for responsible deployment. Effective AI integration enhances decision-making, productivity, and customer satisfaction. Future research should focus on aligning AI with ethical considerations and organizational needs.